Dynamic Response Analysis of Large Shield Tunnel Structure of Shanghai Urban Railway Airport Link under Train Load - CHEN Yangxun (Chengshi guidao jiaotong yanjiu, 2024)
Objective The prefabricated single hole double track large-diameter shield tunnels are more frequently applied in underground rail transit lines, improving the efficiency of underground space utilization. However, the weak connection between the middle partition wall and the tunnel structure affects the operation safety. Therefore, it is necessary to study the dynamic response of the middle partition wall and its top nodes in prefabricated shield tunnels under train dynamic loads. Method Based on the single hole double track large-diameter shield tunnel project of Shanghai Municipal Railway Airport Link, the dynamic response of the internal structure of the prefabricated tunnel under train load is studied by numerical simulation. The safety performance of the middle partition wall and the weak top nodes is verified and analyzed, and the difference between the dynamic responses under single train load and opposite train load are compared. Result & Conclusion Under the action of vertical train load, the segment deformation presents a tendency of change from horizontal duck egg to vertical duck egg, and resumes the initial state of horizontal duck egg after the train load passes by. The convergence reduction value of the lining under the train meeting condition is twice that under the single train condition. The bearing capacity of the top bolt meets the requirements of the standard and can work normally for at least 114 years under the effect of the train dynamic load. Under the action of the train wind load, the horizontal displacement of the top node on the middle partition wall increases, and under the train meeting condition is 2.8 times that under single train condition. The tunnel structure has no resonance risk.